2016
DOI: 10.1074/mcp.m116.058263
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Plasmodium berghei Gametocyte Egressome and Vesicular bioID of Osmiophilic Body Proteins Identifies Merozoite TRAP-like Protein (MTRAP) as an Essential Factor for Parasite Transmission

Abstract: Malaria transmission from an infected host to the mosquito vector requires the uptake of intraerythrocytic sexual precursor cells into the mosquito midgut. For the release of mature extracellular gametes two membrane barriers-the parasite parasitophorous vacuole membrane and the host red blood cell membrane-need to be dissolved. Membrane lysis occurs after the release of proteins from specialized secretory vesicles including osmiophilic bodies. In this study we conducted proteomic analyses of the P. berghei ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 42 publications
(45 reference statements)
4
87
1
Order By: Relevance
“…Activated male Pb MTRAP KO gametocytes formed motile flagella, but they remained intracellular, beating as a thick bundle of flagella, suggesting that they were unable to egress from the PV or the host erythrocyte (Figure 3B; Movie S1). A similar conclusion of lack of egress of P. berghei MTRAP KO was reported in a recently published paper (Kehrer et al., 2016). …”
Section: Resultssupporting
confidence: 89%
“…Activated male Pb MTRAP KO gametocytes formed motile flagella, but they remained intracellular, beating as a thick bundle of flagella, suggesting that they were unable to egress from the PV or the host erythrocyte (Figure 3B; Movie S1). A similar conclusion of lack of egress of P. berghei MTRAP KO was reported in a recently published paper (Kehrer et al., 2016). …”
Section: Resultssupporting
confidence: 89%
“…Proteins containing TSRs are widespread among animals and protozoans and are mostly extracellular or secreted proteins (Tucker, 2004). Also, at least one TSR is contained within all proteins of the TRAP-family, including MTRAP, which was recently found to be important for gametocyte egress from red blood cells (Kehrer et al, 2016a; Bargieri et al, 2016; Morahan et al, 2009) (Figure 1A). In a search for uncharacterized TRAP-family-like TSR-containing proteins, we found a protein with unknown function in the rodent model parasite P. berghei (PBANKA_0707900).…”
Section: Resultsmentioning
confidence: 99%
“…However, the number of non-related proteins that function in egress, and the lack of any clear interaction between these proteins, suggests that even more proteins are involved in the egress of sporozoites from oocysts. It was recently shown that the TRAP-family member MTRAP, previously thought to be important for red blood cell invasion by merozoites, is crucial for the egress of gametocytes from host cells (Kehrer et al, 2016a; Bargieri et al, 2016). We rationalized that similar proteins might also play a role in oocyst egress and searched for distantly related TRAP-like proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Since its development and initial application in 2012 (7), BioID has been cited and/or applied in over 200 PubMed-published articles and has been utilized in several unicellular organisms (see (1215) for examples), mammalian cells (5), plants (16,17), and mice (1820), including compartmental proteomics of a parasitic organism infecting mice (21). Novel or improved applications using BioID ligase have spurred numerous follow-up articles including a smaller version of BioID with improved sensitivity and localization (22), its use for identifying protein-RNA interactions (23), split-BioID studies (24,25), and faster versions of BioID (26).…”
Section: Introductionmentioning
confidence: 99%